A CRITICAL REVIEW OF STRATEGIES FOR PEACE BUILDING IN SCHOOL ADOLESCENTS - Muhammad Nasir Khan , Ehsan Ali , Khalil Akhtar , Syed Shahid Hussain (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Peace building is a worldwide phenomenon. Schools have significant role in peace building in adolescents. The main objective of the study is to critically analyze the adopted strategies of secondary school teachers for peace building in the adolescents. The major objective of the study is the analyze the adopted strategies of the secondary school teachers for peace building in the school adolescents. Participants of the study include secondary school teachers and students of 10th class. The study has been conducted at public sector secondary schools in Punjab province of Pakistan. Qualitative content analysis has been used in the analysis of the collected data. The data has been collected personally by the researcher. Convenient sampling technique has been used in the collection of data. The study finds out the effectiveness of adopted strategies for peace building in adolescents as well. The study is significant for the school administration to review and streamline the policies concerning the peace building in the adolescents. The study is important for revising the school curriculum to enhance the vision of the peace in school adolescents. The study concluded that school curriculum is activity based to enhance the vision of peace in school adolescents. Discussions and individual presentations on peace have been adopted as strategies to enhance the vision of peace in school adolescents. The study recommended that training programs for teachers regarding peace building should be continued at school level. The study recommended that peace activities should be increased in the content of social studies at school level. The study recommended that school climate should be promote regarding the peace promoting activities. The study recommended that education policies should be revised regarding peace building strategies in the school curriculum and teacher training programs.